PENGARUH INTELLECTUAL CAPITAL, KEPEMILIKAN INSTITUSIONAL, KEPEMILIKAN MANAJERIAL DAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP KINERJA KEUANGAN PERUSAHAAN (Studi Pada Perusahaan Manufaktur Sektor Barang Konsumen Primer yang Terdaftar di Bursa Efek Indonesia Periode 2017-2020 - Utami, Fransisca Listyaningsih (Jurnal Ilmu Ekonomi dan Sosial (JIES), 2023)
The company will always strive to achieve its goals by increasing the efficiency and effectiveness of the company. One of the efforts in achieving the company's goals is to increase Intellectual Capital, Institutional Ownership, Managerial Ownership and Corporate Social Responsibility. This research was conducted to obtain empirical evidence regarding the influence of Intellectual Capital, Corporate Social Responsibility, and Institutional Ownership, Managerial Ownership on the company's financial performance.This research data uses secondary data. The population in this study are primary consumer goods manufacturing companies listed on the Indonesia Stock Exchange in 2017-2020. The data is taken from the company's annual report. The sample in this study amounted to 36 companies after being selected using the purposive sampling method. The data analysis method used is descriptive statistical test, classical assumption test, multiple linear regression test and hypothesis testing using SPSS version 24 program.The results of the study show that Intellectual Capital, Institutional Ownership, Managerial Ownership have a positive and significant effect on financial performance (ROE). Meanwhile, Corporate Social Responsibility does not significantly affect financial performance (ROE). However, together Intellectual Capital, Institutional Ownership, Managerial Ownership, and Corporate Social Responsibility positively and significantly affect financial performance (ROE) in primary consumer goods sector companies from 2017 to 2020.